An unlikely hero? Challenging stigma through community engagement. Issue 1 (7th March 2016) - Best, David
Abstract : Purpose: – The purpose of this paper is to describe a high-profile social enterprise in Blackpool, England, called Jobs, Friends and Houses (JFH) that has created a visible social identity of recovery and meaningful activity, to assess how stigma is challenged through active and visible community engagement. Design/methodology/approach: – Case study based on in-depth individual interview and focus group, supplemented by participant in-depth interviews. Findings: – The paper describes one particular incident in which a worker at JFH intervened in a violent attack, possibly saving a woman's life. The paper describes the experiences of internalised stigma and external exclusion being challenged by the development of a positive social identity and a pro-social community role that has high visibility. Data are presented showing the strong social identity experienced by participants and recognised by external stakeholders. Research limitations/implications: – This is a pilot study which uses an opportunistic design and much stronger longitudinal designs will be needed to address the issues raised in the paper. Social implications: – The paper argues that the visibility of the pro-social identity has been central to challenging stereotypes and discriminating attitudes and suggests that a social identity approach may be central to generating and sustaining a recovery community and to confronting and reversing long-held stigmatised attitudes. Originality/value: – The paper is important as it discusses the impact of recovery through engagement in meaningful activities that challenge stigma and exclusion through work. The paper is framed in terms of a social identity model of recovery.